Geo-economic variations in epidemiology, patterns of care, and outcomes in patients with acute respiratory distress syndrome: insights from the LUNG SAFE prospective cohort study. Issue 8 (August 2017) - Laffey, John G; Madotto, Fabiana; Bellani, Giacomo; Pham, Tài; Fan, Eddy; Brochard, Laurent; Amin, Pravin; Arabi, Yaseen; Bajwa, Ednan K; Bruhn, Alejandro; Cerny, Vladimir; Clarkson, Kevin; et al.
Summary: Background: Little information is available about the geo-economic variations in demographics, management, and outcomes of patients with acute respiratory distress syndrome (ARDS). We aimed to characterise the effect of these geo-economic variations in patients enrolled in the Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure (LUNG SAFE). Methods: LUNG SAFE was done during 4 consecutive weeks in winter, 2014, in a convenience sample of 459 intensive-care units in 50 countries across six continents. Inclusion criteria were admission to a participating intensive-care unit (including transfers) within the enrolment window and receipt of invasive or non-invasive ventilation. One of the trial's secondary aims was to characterise variations in the demographics, management, and outcome of patients with ARDS. We used the 2016 World Bank countries classification to define three major geo-economic groupings, namely European high-income countries (Europe-High), high-income countries in the rest of the world (rWORLD-High), and middle-income countries (Middle). We compared patient outcomes across these three groupings. LUNG SAFE is registered withClinicalTrials.gov, numberNCT02010073 . Findings: Of the 2813 patients enrolled in LUNG SAFE who fulfilled ARDS criteria on day 1 or 2, 1521 (54%) were recruited from Europe-High, 746 (27%) from rWORLD-High, and 546 (19%) from Middle countries. We noted significant geographical variations in demographics, risk factors for ARDS, and comorbid diseases. The proportion of patients with severe ARDS or with ratios of the partial pressure of arterial oxygen (PaO2 ) to the fractional concentration of oxygen in inspired air (Fi O2 ) less than 150 was significantly lower in rWORLD-High countries than in the two other regions. Use of prone positioning and neuromuscular blockade was significantly more common in Europe-High countries than in the other two regions. Adjusted duration of invasive mechanical ventilation and length of stay in the intensive-care unit were significantly shorter in patients in rWORLD-High countries than in Europe-High or Middle countries. High gross national income per person was associated with increased survival in ARDS; hospital survival was significantly lower in Middle countries than in Europe-High or rWORLD-High countries. Interpretation: Important geo-economic differences exist in the severity, clinician recognition, and management of ARDS, and in patients' outcomes. Income per person and outcomes in ARDS are independently associated. Funding: European Society of Intensive Care Medicine, St Michael's Hospital, University of Milan-Bicocca.